Suitability assessment of health education brochures in Qassim province, Kingdom of Saudi Arabia - Saulat Jahan; Abdullah M Al-Saigul; Ali M Alharbi; Muzamil H Abdelgadir (Wolters Kluwer Medknow Publications, 2014)
Background: Health education is the cornerstone of primary health care. Health education materials distributed to the community should, therefore, be suitable and effective. The purpose of this study was to evaluate the health education brochures, designed and disseminated by Ministry of Health institutions in the Qassim province. Materials and Methods: The study was a cross-sectional review of health education brochures. We used a structured evaluation form, comprising general information on the brochures and a modified Suitability Assessment of Materials (SAM) score sheet. The SAM consisting of 22 criteria in six groups, includes content, literacy demands, graphics, layout/typography, learning stimulation/motivation, and cultural appropriateness. SAM criteria categorize written material into "superior," "adequate" and "not suitable." Two qualified consultant family physicians evaluated the brochures. Data were analyzed using Epi Info version 3.4 statistical package. Results: We evaluated 110 brochures, the majority of which addressed chronic health conditions such as mental health, diabetes mellitus and hypertension. Seventy-four (67.3%) brochures were evaluated as "adequate," 34 (30.9%) as "not suitable" and 2 (1.8%) as "superior." "Cultural appropriateness" was the highest scoring factor, with 92 (83.6%) brochures falling into either the "superior" or "adequate" category. With regard to "content," 88 (80.0%) brochures fell into either the "superior" or "adequate" category. This was the second highest scoring factor. Graphics was the factor that scored the least. Seventy-five (68.2%) brochures were rated in this factor as "not suitable." Conclusions: Although two-thirds of our brochures were considered "adequate," the majority needed improvement to their graphics and learning stimulation factors. We recommend that guidelines for designing health education brochures should be formulated to improve the quality of health education brochures.